Trade Show Triumph: A Strategic Guide for New Businesses for Better Exposure - Patel, VimalKumar (European Journal of Information and Knowledge Management, 2023)
Trade shows stand as beacons of opportunity for growth and recognition. This whitepaper discusses a roadmap to excel on the trade show stage. Drawing from the experience in prestigious events such as Expo West and Expo East, this guide confers a strategic framework tailored to the unique needs of new businesses looking to benefit from trade shows based on their industry. It includes several frameworks to follow before, during, and after tradeshows to help readers improve their trade show presence and in turn, their industry standing. The paper discusses the challenges and opportunities post-COVID-19, emphasizing the importance of quality over quantity in attendee engagement, a reflection of a 46% rise in attendee quality. It goes on to detail six strategies to master the art of trade show booth engagement. From interactive product demonstrations leveraging the Zeigarnik Effect to gamification rooted in the Pleasure Principle, personalized consultations, storytelling sessions, social media engagement, and feedback stations, each strategy is a powerful tool. Key to success is the flexibility to adapt, as unforeseen circumstances arise. The whitepaper concludes with a three-part checklist, pre-show, during-show, and post-show, serving as a comprehensive roadmap for event success. The post-show follow-up section emphasizes the importance of maintaining connections and fostering lasting relationships. Best Naturals extends an invitation to navigate trade shows with excellence. Recognize the potential of trade show interactions, transform them into long-term business relationships, and secure your place in the future of the nutrition supplement industry.